2021
DOI: 10.3389/fphar.2021.621003
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Bioavailability, Excretion and Metabolism Studies of Akebia Saponin D in Rats: Causes of the Ultra-Low Oral Bioavailability and Metabolic Pathway

Abstract: Background: Akebia saponin D (ASD) has a variety of biological activities and great medicinal potential, but its oral bioavailability is so low as to limit its development. Its pharmacokinetic profiles and excretion and metabolism in vivo have not been fully elucidated. This study was an attempt in this area.Methods: A simple LC-MS/MS method to simultaneously quantify ASD and its metabolites M1∼M5 in rat plasma, feces, urine and bile was established with a negative ESI model using dexketoprofen as the internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…At the same time, the extensive metabolism and distribution of drugs in vivo might be one of the reasons for the low bioavailability. 17 However, there was controversy about the absolute bioavailability of glabridin in vivo. 1 Ito et al 12 believe that glabridin has high oral bioavailability, which was based on the evaluation of the Caco-2 cell model in vitro and the plasma exposure of glabridin after oral administration in different dosage forms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the extensive metabolism and distribution of drugs in vivo might be one of the reasons for the low bioavailability. 17 However, there was controversy about the absolute bioavailability of glabridin in vivo. 1 Ito et al 12 believe that glabridin has high oral bioavailability, which was based on the evaluation of the Caco-2 cell model in vitro and the plasma exposure of glabridin after oral administration in different dosage forms.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the extensive metabolism and distribution of drugs in vivo might be one of the reasons for the low bioavailability . However, there was controversy about the absolute bioavailability of glabridin in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The pentacyclic saponins can produce deglycosylation reactions in electric fields, as well as in intestinal flora in vitro [ 32 , 33 , 34 ]. On the other hand, a similar reaction also occurs in saponins in vivo [ 35 ]. However, the mechanism for this phenomenon needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…P2 and P4 are the signature active ingredients of JQG and YZZ, respectively [34,35]. Due to low oral bioavailability and a short half-life, the components with high responses in vitro (C13, C24, C30, and C31) were not found as prototypes or metabolites in vivo [36][37][38]. By studying the metabolic pathways in detail, we found that the metabolites were mainly from glucuronidation, sulfation, hydroxylation, and demethylation reactions of the flavonoids in YQD.…”
Section: Identification Of Absorbed Components In Rat Plasmamentioning
confidence: 96%